Statistical summability (C, 1) for sequences of fuzzy real numbers and a Tauberian theorem - Altin, Y.; Mursaleen, M.; Altinok, H. (Ios Press, 2010)
Statistical convergence for sequences of fuzzy real numbers has been studied by various authors. In this paper we study the concept of statistical summability (C, 1) for fuzzy real numbers which for real numbers was introduced by Moricz [18]. We also construct some interesting examples.
Keywords: Fuzzy numbers; statistical convergence; Tauberian theorem